Ownership structure and firm performance in the Egyptian manufacturing sector - Ahmed Fayez Abdelgouad; Christian Pfeifer; John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
We use the World Bank enterprise survey for the Egyptian manufacturing sector to study the correlation between the ownership structure (private vs. public, Egyptian vs. Arab foreign vs. non-Arab foreign) and firm performance, which we measure as sales per worker, capacity utilization, and net profit rate. Our main findings indicate that (1) productivity differences between Egyptian private and public firms are not significant, but firms with public ownership have a lower capacity utilization and a lower net profit rate than private firms, (2) firms with private Arab and private non-Arab foreign ownership are significantly more productive and have a higher capacity utilization than purely Egyptian owned firms, and (3) differences between Arab and non-Arab foreign ownership are not significant for productivity and capacity utilization, but firms with non-Arab foreign ownership have a higher net profit rate than firms with Arab foreign or Egyptian owners.
Keywords: 330